Oxygen permeation properties of novel BaCo0.85Bi0.05Zr0.1O3−δ hollow fibre membrane. (23rd February 2018) - Qiu, Zhenghui; Hu, Yadi; Tan, Xiaoyao; Hashim, Siti Salwa; Sunarso, Jaka; Liu, Shaomin
Highlights: BaCo0.85 Bi0.05 Zr0.1 O3−δ hollow fibre (BCBZHF) membrane was developed. BCBZHF membrane displays very high oxygen flux up to 7.3 cm 3 cm −2  min −1 . Oxygen permeation through the membrane is controlled by surface reactions. BCBZHF membrane possesses high CO2 resistance. Abstract: In this work, we characterized and tested the oxygen permeation properties of BaCo0.85 Bi0.05 Zr0.1 O3−δ (BCBZ) hollow fibre membranes fabricated by a combined phase inversion for spinning and sintering route using polyetherimide (PEI) as the polymer binder. The powder X-ray diffraction results showed that the BCBZ powder for spinning had to be calcined at around 950 °C to form a hexagonal phase structure, while the hollow fibre precursors were sintered at 1150–1200 °C to form the cubic perovskite structure for oxygen permeation. It displayed the highest oxygen flux of 7.3 cm 3 (STP) cm −2  min −1 at 950 °C under an air/He gradient. The theoretical correlation of the oxygen fluxes at different operating conditions showed that the oxygen permeation through BCBZ fibre was limited by surface exchange reactions. Carbon dioxide (CO2 ) resistance of BCBZ hollow fibre was tested by exposing it to alternating different sweep gas containing helium (He), 20% CO2 in He, 80% CO2 in He, and pure He. Despite the significant reduction in oxygen fluxes upon subjected to CO2 -containing sweep gases due to the strong CO2 sorption on the membrane surface, no permanent damage on the membrane was detected and the original flux could be recovered at the end of the 105-h test once the sweep gas was switched back to helium. This result clearly highlights the high CO2 resistance of BCBZ hollow fibre membrane due to the presence of Zr 4+ with higher acidity than Co 2+ in BCBZ perovskite lattice. High CO2 tolerance enables the membrane use as membrane reactors for more advanced applications where the presence of CO2 -containing atmosphere is unavoidable.